2011
DOI: 10.4319/lo.2011.56.6.2103
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of acclimation to Microcystis on the selective feeding behavior of the calanoid copepod Eudiaptomus gracilis

Abstract: We tested the hypothesis that calanoid copepods would adapt to extended periods of Microcystis exposure by increasing selective feeding on alternative food. Copepod (Eudiaptomus gracilis) clearance rates were compared before and after a 5-d acclimation to Microcystis aeruginosa using paired food mixtures containing a microcystinproducing (MC+) or -lacking (MC2) strain and the green alga Chlamydomonas reinhardtii. Acclimation reduced the ingestion of Microcystis, increased ingestion of Chlamydomonas, and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 45 publications
1
41
1
Order By: Relevance
“…, 2010). In addition, in warmer climates, copepods typically dominate the crustacean zooplankton year‐round and may indirectly facilitate cyanobacteria by grazing on competing phytoplankton (Ger, Panosso & Lürling, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…, 2010). In addition, in warmer climates, copepods typically dominate the crustacean zooplankton year‐round and may indirectly facilitate cyanobacteria by grazing on competing phytoplankton (Ger, Panosso & Lürling, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Copepods show a high degree of feeding selection by maximising the ingestion of the most nutritious food from a mixture of particles using chemosensory detection to differentiate the size, nutrition and digestibility of encountered particles (DeMott, 1989;Kleppel, 1993;Tackx et al, 2003;Tirelli & Mayzaud, 2005). When cyanobacteria are encountered, copepods use different cyanobacterial secondary metabolites (such as microcystin, lipopolysaccharides and unidentified lipophylic compounds) as detection cues to avoid ingestion (Kurmayer & Juttner, 1999;Engstrom et al, 2000;Ger, Panosso & Lurling, 2011). Consequently, selective feeding usually allows copepods uninhibited feeding on alternative food in the presence of toxic cyanobacteria, resulting in the grazer coexisting with blooms (Bouvy et al, 2000;Koski et al, 2002).…”
Section: Macroevolutionary Adaptations To Cyanobacteria (Interspecifimentioning
confidence: 99%
“…Another study showed how a 5-day exposure to cyanobacteria enhanced the feeding selectivity for 'good food' in the calanoid copepod Eudiaptomus gracilis (Ger et al, 2011). Clearly, induced responses to short-term cyanobacteria exposure can improve the tolerance traits of individual zooplankton and may be common in nature.…”
Section: Induced Physiological or Behavioural Adaptations (Phenotypicmentioning
confidence: 99%
“…The δ Pace & Carman 1996, Buffan-Dubau & Carman 2000. Furthermore, when feeding conditions are unfavorable, harpacticoids can adjust their feeding rate (Montagna et al 1995), may shift to alternative food sources as observed for planktonic copepods (Ger et al 2011), or survive on their lipid reserves (Weiss et al 1996). The copepod's fatty acid (FA) profile, and in particular their high levels of the highly unsaturated FAs (PUFA) 20:5ω3 (eicosapentaenoic acid; EPA) and 22:6ω3 (docosahexaenoic acid; DHA) contribute to the nutritional value of copepods for fish (Nanton & Castell 1998, Bell et al 2003.…”
Section: Introductionmentioning
confidence: 99%